Washington View: From conflict to cooperation: 9/11 Day. (September 2021) - Ferguson, Maria
In a time of great political division, the 9/11 National Day of Service and Remembrance stands as an example of how Americans can turn tragedy and conflict into an opportunity for collective action. Maria Ferguson reflects on what she has learned from her work with the organization that established what is now the largest national day of service in the United States .